The Putative Role of Astaxanthin in Neuroinflammation Modulation: Mechanisms and Therapeutic Potential - Wang, Shuai; Qi, Xin (Frontiers in Pharmacology, 2022)
Neuroinflammation is a protective mechanism against insults from exogenous pathogens and endogenous cellular debris and is essential for reestablishing homeostasis in the brain. However, excessive prolonged neuroinflammation inevitably leads to lesions and disease. The use of natural compounds targeting pathways involved in neuroinflammation remains a promising strategy for treating different neurological and neurodegenerative diseases. Astaxanthin, a natural xanthophyll carotenoid, is a well known antioxidant. Mounting evidence has revealed that astaxanthin is neuroprotective and has therapeutic potential by inhibiting neuroinflammation, however, its functional roles and underlying mechanisms in modulating neuroinflammation have not been systematically summarized. Hence, this review summarizes recent progress in this field and provides an update on the medical value of astaxanthin. Astaxanthin modulates neuroinflammation by alleviating oxidative stress, reducing the production of neuroinflammatory factors, inhibiting peripheral inflammation and maintaining the integrity of the blood-brain barrier. Mechanistically, astaxanthin scavenges radicals, triggers the Nrf2-induced activation of the antioxidant system, and suppresses the activation of the NF-κB and MAPK pathways. With its good biosafety and high bioavailability, astaxanthin has strong potential for modulating neuroinflammation, although some outstanding issues still require further investigation.